IT Governance Awareness and Practices: an Insight from Malaysian Senior Management Perspective - Yap , May Lin; Noor Habibah Arshad; Halilah Haron (2010)
While corporate governance is now receiving due attention in the Asian region, IT governance (ITG) does not appear to be given much credence even though business processes today mandate IT. It is observed that awareness and practices of ITG do not seem to be widespread in the region. Using senior management sample data from Malaysian organizations, a study was conducted to determine the awareness and practices of ITG. Contrary to observation, findings indicated that Malaysian businesses appeared to exhibit awareness but ITG was only partially practiced. There was positive correlation between both concepts. Although the association was not causal, it revealed the potential tendency for awareness to cascade down to practices in an operating environment. ITG practices may be strengthened through senior management commitment and involvement, oversight committees, and real-world issues experienced by organizations such as the focus on IT creating tangible value to real stakeholders and the strategic alignment of IT to include the real business environment. [ABSTRACT FROM AUTHOR]